Extrapulmonary tuberculosis - Heysell, Scott (Henry Stewart Talks, 2022)
Clinical case of TB from Tanzania, Pathophysiology of extrapulmonary TB, The epidemiology of extrapulmonary TB, Diagnostic considerations, Relationship between HIV and TB, Clinical manifestations of TB disease, Therapeutic considerations